Ruptura amorosa y su afectación en la conducta de un adulto de 26 años de la ciudad de Babahoyo - Sancan Rodriguez, Yuriko Damaris (2023)
In this present study, the investigation of love breakup and its affectation in the behavior of a 26-year-old adult was carried out. It was verified that the breakup of a couple is a topic that currently prevails and that is due to the consequences that occurred after a breakup that can occur, by third parties, infidelity, deceit or betrayal, causing the other people involved to be injured, causing their emotions to change drastically reflecting in an unhealthy way such as anger, anger causing these people to have irrational behavioral changes. In this study, a psychotherapeutic intervention was proposed with a rational emotional behavioral approach, with the purpose of restoring their cognitive processes, their irrational thoughts that intervene in the patient's behavior, for which, with the help of the tests, carried out in each session, detected that the adult is very controlling, perfectionist, and obsessive in the workplace together with the staff, causing this to affect his life. With different techniques, it was possible to address the current situation that the patient is experiencing, interfering in his thought processes and emotional state, with the aim of improving mental health and that this is reflected in his interpersonal relationships.